Challenges of Generation Z in Maintaining Local Culture As a National Identity in Globalization Era - Muthiara Dharma, Ni Made; Dharmapurusa, Avanindra Amrtani; Nathanael, Kevin; Rumambo Pandin, Moses Glorino (Jurnal Pendidikan Tambusai, 2021)
The era of globalization has brought Generation Z to experience expansion of contact with modern outside cultures so that local culture begins to erode because Generation Z prefers to absorb foreign cultures which are considered more practical. This will endanger the existence of local culture as the national identity of the Indonesian nation. This study aims to find out what kind of challenges need to be considered by Generation Z in maintaining local culture as the national identity of the Indonesian nation. This research used a qualitative method by obtaining data based on literature review by collecting data from 10 scientific journals related to the theme. There are several challenges in maintaining local culture such as, Generation Z are very easily influenced by foreign cultures so that they love and respect foreign cultures more than local cultures, the lack of awareness of the younger generation to maintain local culture, the lack of filtering of foreign cultures, cultural invasion, until the recognition of the local culture of the Indonesian nation by other countries.